2012
DOI: 10.1002/glia.22380
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids alleviate proinflammatory conditions by modulating innate immune response in muller glia during inflammation

Abstract: Muller cells play a prominent role in inflammatory conditions of the retina. They are part of the retinal innate immune response. The endocannabinoid system functions as an immune modulator in both the peripheral immune system as well as the central nervous system. We hypothesized that the neuroprotective ability of exogenous endocannabinoids in the retina is partially mediated through Muller glia. This study reports that exposure to endocannabinoids in activated but not resting primary human Muller glia inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…5B), almost as much as addition of AEA. Earlier work from the authors had identified the mitogen-activated protein kinases (MAPK) pathway as a fulcrum during inflammation in Mu¨ller glia (Krishnan and Chatterjee, 2012), with the phosphatase, MKP-1 emerging as critical in limiting excessive production of pro-inflammatory factors. Existing reports show the inhibition of iNOS expression via the MKP-1/MEK/ERK pathways (Liu et al, 2013).…”
Section: Mkp-1 Is Essential For Aea Action To Regulate Inos Levelmentioning
confidence: 99%
See 4 more Smart Citations
“…5B), almost as much as addition of AEA. Earlier work from the authors had identified the mitogen-activated protein kinases (MAPK) pathway as a fulcrum during inflammation in Mu¨ller glia (Krishnan and Chatterjee, 2012), with the phosphatase, MKP-1 emerging as critical in limiting excessive production of pro-inflammatory factors. Existing reports show the inhibition of iNOS expression via the MKP-1/MEK/ERK pathways (Liu et al, 2013).…”
Section: Mkp-1 Is Essential For Aea Action To Regulate Inos Levelmentioning
confidence: 99%
“…AEA was used at 10 lM unless mentioned otherwise. We had earlier optimized that exposure to 10 lM AEA is necessary for regulation of pro-inflammatory cytokines in Mu¨ller cells (Krishnan and Chatterjee, 2012). Five micromole DAF-2DA and 10 mM Lucifer Yellow were used for imaging studies.…”
Section: Primary Mü Ller Glia Culture and Cell Treatmentmentioning
confidence: 99%
See 3 more Smart Citations